Echocardiographic Parameters of Right Ventricular Diastolic Function in Repaired Tetralogy of Fallot Are Associated with Important Findings on Magnetic Resonance Imaging. (27th April 2015) - Maskatia, Shiraz A.; Morris, Shaine A.; Spinner, Joseph A.; Krishnamurthy, Rajesh; Altman, Carolyn A.
Abstract Background Right ventricular (RV) dilation, RV dysfunction, RV outflow tract obstruction, and branch pulmonary artery stenosis are risk factors associated with the need for future surgical or catheter‐based intervention commonly assessed by cardiac magnetic resonance in patients with tetralogy of Fallot who have undergone initial repair. The ability of echocardiography to predict the presence of these risk factors is limited. Objective We aimed to determine the association between echocardiographic parameters of right ventricular diastolic dysfunction and risk factors for intervention as identified on cardiac magnetic resonance imaging (CMR). Design We reviewed all echocardiograms and CMRs performed at our institution within 1 year of each other in patients with repaired tetralogy of Fallot. We evaluated patients for the following: RV systolic dysfunction (RV ejection fraction <45%), RV dilation (right ventricular end‐diastolic volume ≥160 mL/m2), and RV obstruction (RV outflow tract gradient ≥3 m/s by echocardiogram or branch pulmonary artery stenosis assessed by CMR). We evaluated for associations between the above CMR findings and echocardiographic parameters of diastolic function. Results CMR and echocardiographic images performed between March 2007 and March 2012 were available in 99 patients. RV obstruction was associated with lower E/A ratio (P = .02), E/A reversal (P = .02), and prograde end diastolic pulmonary flow (P < .01). Low tricuspid annular a′ and low septal s′ were associated with lower RV ejection fraction (P < .01, P < .01). Elevated E/e′ was associated with higher RV end diastolic volume (P = .04). In predicting the presence of any of the evaluated risk factors for future intervention, TV E/e′ ≥4.7 had positive predictive value (PPV) of 86% and negative predictive value (NPV) of 50%, TV E/A reversal had PPV of 89% and NPV of 34, and prograde end diastolic pulmonary flow on echocardiogram had PPV of 91% and NPV of 38%. Conclusions Echocardiographic parameters of diastolic dysfunction have a reasonable PPV but poor NPV for predicting clinically significant risk factors identified by CMR.